RANCANG BANGUN ALAT PENGUKUR DAN SISTEM JARINGAN DATA CO2 DI INDONESIA BERBASIS WEB - Asif Awaludin; Ginaldi Ari Nugroho; Chunaeni Latief; Afif Budiyono (Jurnal Sains Dirgantara, 2010)
A web-based CO2 measurement device and a data network system in Indonesia which consist of the CO2 measurement device, the local data processor system, and the central data processor system has been built. The CO2 measurement device consist of the GMM220 CO2 sensor module from Vaisala and the data logger system. The data logger output consists of location, time, date, CO2 concentration, and input voltage, which packed all up in one data form with RGPGHG as the data header. The data logger system store the data into SD Card memory and ends it to the local data processor system. The CO2 Monitor Software in the local data processor system processes the data and display the graphical data which shows the maximum, minimum and average values of the data, and also sends the data to the central data processor system. The central data processor system displays data from several local data processor systems in the form of real time web-based graphical data and text, so the internet users can access and download its data. The development result device has been applicated in Kototabang, and the CO2 measurement device has been connected as well to the central data processor system in Bandung via the internet network to perform the web-based CO2 data network system in Indonesia. According to the data stored by the central data processor system for the periode of 1 - 26 March 2010, it shows that the CO2 concentration in Kototabang have an average of 403,5 ppm, with the maximum of 476,9 ppm and the minimum of 364,7 ppm. While the CO2 concentration in Bandung have an average of 397,2 ppm, with the maximum of 502,5 ppm and the minimum of 325,3 ppm. Key words: Data logger, CO2 sensor, Web-based interface